5-Lipoxygenase, leukotrienes biosynthesis and potential antileukotrienic agents - Jampilek, Josef; Dolezal, Martin; Opletalova, Veronika; Hartl, Jiri (Current medicinal chemistry, 2006)
Leukotrienes play an important role in the inflammatory process accompanying allergic diseases of respiratory, gastrointestinal and dermatological systems. Leukotrienes are generated from arachidonic acid as a result of the 5-lipoxygenase action. This paper deals with 5-lipoxygenase action mechanism and the following biosynthesis of all leukotrienes. In this article, potential antileukotrienic agents are classified according to their mechanism of action. The original antileukotrienic compounds of the Research Institute for Pharmacy and Biochemistry in Prague (VUFB), Czech Republic are presented in a separate chapter of the paper.
Keywords: Leukotriene Antagonists; substrátová specifita; Arachidonic Acid; antiflogistika; lidé; Leukotrienes; zvířata; Anti-Inflammatory Agents; Humans; leukotrieny; Substrate Specificity; kyselina arachidonová; arachidonát-5-lipoxygenasa; Lipoxygenase Inhibitors; inhibitory lipoxygenas; Arachidonate 5-Lipoxygenase; Anti-Asthmatic Agents; antiastmatika; antagonisté leukotrienů; Animals